ANTARA KEADILAN DAN KEPASTIAN HUKUM: KONFLIK YUDISIAL MAHKAMAH AGUNG –MAHKAMAH KONSTITUSI (STUDI KASUS PENINJAUAN KEMBALI) - Cindy Cherya (Problematika Hukum, 2018)
Although the positions of the Supreme Court and the Constitutional Court are parallel as stipulated in Article 24 paragraph (2) of the 1945 Constitution, these two institutions are still limited by different demarcation lines of authority. However, on a practical level, there are often conflicts between the boundaries of their relationship and authority, for example related to judicial review. This polemic stems from the Constitutional Court Decision Number 34/PUU-XI/2013 which in its decision annulled “Article 268 paragraph (3) of Criminal Procedure Code. As for Article 268 paragraph (3): "a request for review of a decision can only be made once". Historically and philosophically, judicial review was born as a form of state responsibility in protecting the interests and restoring justice and the rights of prisoners who have been illegally confiscated by the state. With the Constitutional Court's Decision, judicial review can be carried out more than once, which has the potential to make the trial process protracted and not in accordance with the litis finiri oportet principle (every case must have an end). Following up on the juridical implications, the Supreme Court issued a Supreme Court Circular Number 7 of 2014 which again contradicted the Constitutional Court's Decision Number 34/PUU-XI/2013 by allowing the judicial review to be submitted only once. The purpose of this study is to describe the relevance of the Constitutional Court Decision Number 34/PUU-XI/2013 and Supreme Court Circular Number 7 of 2014 regarding the Judicial Review in the perspective of justice and legal certainty and its implications for the litis finiri oportet principle in criminal procedural law in Indonesia. Sources of legal materials used in this research are primary legal materials in the form of legislation and court decisions as well as secondary legal materials in the form of legal literature and research results.